Enhancing Sport Education Students’ Speaking Performance through Assigned Topics in STOK Binaguna Medan - Arsi Zahiri; Amminiyani; Heridayani (LingPoet: Journal of Linguistics and Literary Research, 2026)
Speaking proficiency is an essential skill for students in sports education, as their future professional roles require the capacity to clarify sports regulations, deliver coaching directives, motivate athletes, outline training programs, and communicate effectively in academic or professional settings. In English as a Foreign Language (EFL) contexts, speaking poses considerable obstacles as learners must simultaneously manage vocabulary, pronunciation, grammar, fluency, comprehension, and confidence (Burns, 2019; Yu et al., 2024). Indonesian EFL learners often face speaking difficulties stemming from limited vocabulary, inadequate fluency, pronunciation concerns, reduced confidence, and speaking anxiety (Marlia et al., 2023; Wijaya, 2023). This study aims to examine the influence of designated subjects on the speaking performance of sports education students at STOK Binaguna Medan. The study utilized a quasi-experimental approach that included a pre-test and post-test control group. Forty students were assigned to an experimental group and a control group. The experimental group received instruction in speaking on specific sport-related topics, while the control group participated in conventional speaking coaching. The speaking examination was assessed based on fluency, vocabulary, pronunciation, grammar, and comprehension. The findings indicate that the experimental group showed superior advancement compared to the control group. Students who interacted with designated topics demonstrated greater conceptual organization, enriched vocabulary, heightened confidence, and higher speaking fluency. The study demonstrates that designated subjects effectively improve speaking performance in sports education by providing preparation time, contextual relevance, frequent practice, and structured speaking opportunities.